Minors with disabilities from migratory routes: studies and researches in educational, scholastic and social contexts - Ivana Bolognesi; Roberto Dainese (Educazione Interculturale, 2020)
N. 2/2020 of Educazione interculturale aims to address an issue still poorly investigated today that concerns the presence and integration of children with disabilities from migratory contexts. If there is already research and extensive literature on adults and minors of foreign origin and on the integration of people with disabilities, those aimed at understanding the implications of cultural belonging and disability in the process of identity building of such people are still scarce (Goussot, 2010; Bolognesi, 2011; Caldin, 2012; Martinazzoli, 2012; Friso e Pileri, 2019). This monographic issue is therefore intended to bring attention to this specific theme which should be considered both as an object of research, but also as an educational intervention, a theme to be deepened and disseminated not only in the academic field, but also in school, social, professional and health contexts which are daily engaged in building integration and inclusion processes.